Study of Enzymatic Activity of Fungi Isolated from Spoiled Bread Found in Contaminated Soil Around Birnin Kebbi City, Kebbi state Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2022)
enzymes ranging from biochemical substances that are of industrial significance that includes by-products of both primary and secondary metabolites. Ethanol, citric acid, gluconic acid, itaconic acid, amino acid, Vitamins, nucleotides and polysaccharides provide examples of primary metabolites produced by fungi. Antibiotics such as penicillin, cephalosporin, fusidic acid and griseofulvin are important secondary metabolites. Fungi are well known as a source of antibiotics but new therapeutic compounds with novel pharmacological activities have been developed in recent years. Loaves of spoilt Bread recruited for this study were collected from different Areas of Birnin Kebbi town and exposed for 7 days in different Areas and are assessed daily. Potato Dextrose Agar (PDA) was used as a culture medium for the isolation. Three fungal species were isolated from Bread samples from contaminated sites using Potato Dextrose Agar. Characterization was based on classical microscopic and macroscopic techniques of color margin and elevation of pure colonies. The consumption of the spores of Fungi that is associated with the spoilage of Bread leads to an increase in Airborne yeasts infections, previous studies had shown that most fungi species that grow on bread stand a major factor of respiratory infection due to their cosmopolitans in the distribution of spores.
Keywords: Bread; Enzymes; Aspergillus; Penicillium; Rhizopus